How does SDG4 connect to the post-2015 EFA agenda? - SOH, Ki-Joon (KDI School, 2015)
Before the international community adopted the Sustainable Development Goals (SDGs), the international educational community agreed on the Muscat Agreement, with some similar but ultimately different goal and targets. Based on a stakeholder analysis on accountability developed by Romzek and Dubnick (1987), this paper argues that while political accountability was primary and professional accountability was secondary in developing the post-2015 agendas for both UN and UNESCO, there was a stronger professional accountability for UNESCO, which resulted difference in input targets and the scope of the post-2015 educational agenda. The author argues this was possible due to the combination of both representatives of member states and international organizations participating in the discussion process as equal members, as well as an atmosphere where active debate was allowed during the consultation process.
Thesis(Master) --KDI School:Master of Public Policy,2015